APLIKASI SELEKSI KENAIKAN JABATAN PADA PT. XYZ DENGAN ALGORITMA PROFILE MATCHING DAN TES PAULI - Muhammad Alil Mafahir (Fakultas Teknik Universitas Negeri Surabaya, 2019)
Filling vacant positions in the promotion process often have difficulty because offering the candidate who can occup that position by of profile matching the employees profile and positions are less well defined .To minimize these obstacles r equire a decision support system that can analyze several employees who fit the profile of existing positions. Decision support system for the profile matching process is created based on the data contained in the PT. The XYZ. The Profile Matching process is done to determine the employee recommendation of the promotion process bassed on 3 aspects of Intellectual Capacity , Work Attitudes and Behaviour. The results of this process in the form of ranking employees as recommendations for decision makers to select suitable employees in vacant positions. From the results of the implementation of the system , it was concluded that the using this software can help the decision-making process to the promotion process